ANALYSIS OF FACTORS INFLUENCING SMALL BUSINESS DEVELOPMENT BASED ON AN ECONOMETRIC MODEL AND FUTURE FORECASTING - Usmonova, Nodirakhon (THE INNOVATION ECONOMY, 2026)
This scientific article analyzes the main economic factors influencing the development of small enterprises in the Andijan region using econometric modeling methods. The study evaluates the impact of factors such as investment volume, bank loans, tax policy, labor resources, and infrastructure level on small business development based on statistical data. A multiple regression model is constructed to determine the relationship between variables. Additionally, future development trends are forecasted using time series analysis. The results of the study are significant for improving regional economic policy and developing effective mechanisms to support small enterprises.